Development of Bench-Scale Direct Contact Membrane Distillation System for Treatment of Palm Oil Mill Effluent - Yi, C. Wan; Xin, N. Hwee; N. M., Mohktar (Universiti Teknologi Malaysia, 2023)
The oil palm industries generate large amounts of effluent that can cause pollution and, as a result, pose serious threats to the environment. Recently, membrane distillation (MD) has been identified as a potential candidate for treatment of palm oil mill effluents (POME). This is because the release of POME at high temperature may reduce the need to preheat the effluent prior to operation. The objective of this article is to manufacture a bench-scale MD system and assess the performance of the system in POME treatment. This project started with the design of a process and instrumentation diagram (P&ID) and continued with the fabrication part. Subsequently, the performance of the direct contact membrane distillation (DCMD) system was tested using POME as a feed solution. Three different feed temperatures (55 °C, 65 °C and 75 °C) were analyzed during the testing. The results obtained show that the permeate flux increased with the increase of feed temperature with the highest flux is 10.76 kg/m2.hr. More than 85% of pollutants including ammonia nitrogen, color, chemical oxygen demand (COD) and turbidity were rejected. This shows that the system is capable of treating POME and producing high quality permeate water.